Idobata-Nagaya: a community housing solution for socially isolated older adults following the great East Japan earthquake - Abe, Toshiki; Saito, Hiroaki; Moriyama, Nobuaki; Ito, Naomi; Takita, Morihito; Kinoshita, Yuri; Ozaki, Akihiko; Nishikawa, Yoshitaka; Yamamoto, Chika; Zhao, Tianchen; Sato, Mika; Tsubokura, Masaharu (Frontiers in Public Health, 2023)
Following the Great East Japan Earthquake, the living environment of socially isolated older adults has become a pressing concern. In response, Nagaya, a collective housing program, was established in Soma City, Fukushima, Japan to address social isolation among older adults and support their long-term health. This study aimed to identify characteristics of individuals in Nagaya and examine the sustainability of this initiative. We conducted a retrospective analysis of residents who were relocated to Nagaya, emphasizing their characteristics, the continuity of their stay in Nagaya, and their care certification levels, using data up to December 31, 2022. We employed Kaplan-Meier curves to analyze the duration for which residents continued to reside in Nagaya and the time leading up to the requiring care-level certification. Of 65 people who moved to Nagaya after the disaster, 30 people (45%) continued to live there, 21 (34%) died during their stay, and 14 (21%) moved out. The overall duration of occupancy averaged 6.39 years (SD 3.83 years). The proportion of requiring care-level certification occurrences per person-year was 0.0577 for those without care certification and 0.3358 for those with requiring support level at the time of moving in. In summary, Nagayastyle communal housing may offer suitable living environments for older adults with diverse needs during disasters and serve as a valuable tool for developing public policies in aging societies.